Zero emissions in 10 years? Contradictions in Paris Agreement and their solution. On precautionary principle and overrated climate scenarios. - Ekardt, Felix; Zorn, Anika; Wieding, Jutta (Momentum Quarterly, 2018)
The Paris Agreement of December 2015 is subject to much criticism. This however neglects its very ambitious objective which limits global warming legally binding to 1.5 to 1.8 degrees in comparison to pre-industrial levels. This article shows, based on the overlap of unanswered questions for prognoses in natural science and the legal precautionary principle, that this objective indicates a legal imperative towards zero emissions globally within a short timeframe. Furthermore, it becomes apparent, that policies need to be focussed on achieving the 1.5-degree-temperature limit. And from a legal standpoint with regard to existential matters only those policies are justified that are fit to contribute to reaching the temperature limit with high certainty. This creates a big challenge even for the alleged forerunners of climate policies Germany and EU. Because, according to the objective, EU and Germany have to raise the level of ambition in their climate policies rapidly and drastically.